The Stress Level of Parents with Children Undergoing Chemotherapy for Cancer - Dian Nur Wulanningrum; Ade’ Rahma Mardani; Dewi Suryandari; Diyanah Syolihan Rinjani Putri (Jurnal Penelitian Perawat Profesional, 2025)
Childhood cancer is a non-communicable disease that affects children under 18 years of age, characterized by abnormal cell growth that spreads to surrounding tissues. Chemotherapy is one of the treatments for children with cancer. Chemotherapy works by killing cancer cells using anticancer drugs, which can cause physical, psychological, and social side effects for both patients and their families. Parents are one of the most important components in a family for a child, especially those with cancer. Chemotherapy in children with cancer often requires a long period of treatment, which can lead to psychological problems for parents, such as stress. Stress experienced by parents of children with cancer should be identified early to minimize further risks. Objective to describe the stress levels of parents with children undergoing chemotherapy. Method: This study used a quantitative design with a descriptive approach. A total of 35 respondents were included using total sampling. The study was conducted in the Tulip 6 ward of Dr. Moewardi General Hospital. The instrument used in this research was the PSS-10 questionnaire. Data were analyzed using univariate analysis. The findings showed that the majority of parents who accompanied their children during chemotherapy experienced moderate stress levels, with 24 respondents (68.6%). Parents accompanying children with cancer undergoing chemotherapy experienced a moderate level of stress.